Treatment of pseudophakic aqueous misdirection syndrome - Joel-Benjamin Lincke; Nathanael Häner; Megir Schawkat; Martin S. Zinkernagel; Jan Darius Unterlauft (Scientific Reports)
Abstract To describe the management and clinical course of 12 cases of pseudophakic aqueous misdirection syndrome (AMS). Twelve eyes of 12 Patients diagnosed with pseudophakic AMS between 2021 and 2022 were included. Best-corrected visual acuity, refraction, intraocular pressure (IOP), anti-glaucomatous medication, spectral domain ocular coherence tomography (SD-OCT) and postoperative complications were evaluated. The mean time of AMS onset was 888 days (SD ± 1210, range: 1–2920) after cataract surgery. Treatment with IOP-lowering medication alone was non-sufficient in all followed cases. Laser iridotomy (LIT) was performed in 4 eyes and led to resolution of AMS in 3 eyes. Nine eyes were treated surgically with 23-gauge pars plana vitrectomy and irido-zonulectomy. The most common postsurgical complication was cystoid macular edema (CME), occurring in 30% of cases. AMS is a rare but serious complication after cataract surgery, which can occur many years later. While LIT can be tried as first line treatment, pars plana vitrectomy with irido-zonulectomy is often required to ultimately control IOP in these eyes. A common complication after vitrectomy is CME.